Assessing Public Preferences for Street Furniture Design in the Kayutangan Heritage Corridor, Malang: Toward Context-Sensitive Urban Revitalization - Azizah, Novia; Santosa, Herry; Wulandari, Lisa Dwi (RUAS, 2026)
The design of street furniture in urban heritage corridors significantly influences the social and cultural design of its urban life. Kayutangan, a cultural heritage site in Malang city, has undergone several phases of revitalization. However, the suitability of street furniture elements and cultural heritage value remains a concern. This study aims to evaluate public preferences for street furniture elements in the Kayutangan corridor area. This study employs a descriptive quantitative method using a Likert scale questionnaire, involving 115 respondents. The data were analysed using mean scores, ANOVA, independent t-test samples, and multiple regression analysis. The research variables consist of: aesthetics, safety, comfort, accessibility, functionality, suitability, and the historical corridor area appeal. The result shows that the functionality variable becomes an important element of street furniture in assisting users' activity. Lamp design in heritage style is found to have historical regional characteristics, and the shelter does not reach acceptable user preferences. Multiple regression analysis shows that heritage character compatibility is the most important factor for people's preferences. This finding provides evidence-based guidelines for designing street furniture that is historically context-sensitive, thus facilitating the revitalization of urban areas.